THE IMPORTANCE OF DOING AN ICE-BREAKING BEFORE CORE LEARNING ACTIVITIES - Farah Amaliyah Yuwono; Rahmania Sri Untari; Lintang Suminar; Ristananda Izzul Muslimin Syifa (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study discussed the importance of doing an Ice-Breaking before Core Learning Activities to enhance students’ learning motivation level for Tenth grade students at SMKN 2 BUDURAN SIDOARJO. This research objectives to avoid of students’ problem that exhibiting low enthusiasm and motivation in their learning endeavors. The researchers employed a qualitative descriptive methodology. The techniques for data collection encompassed observation, doing three categories of ice-breaking, and documentation only. The findings showed the data of participants consisted around +30 students from various classes, specifically X DKV, RPL, and BD classes and showed the attachment of three categories of ice-breaking techniques were applied across several classes, specifically "Hold Friends' Shoulder", "Who Faster, They Got it!", and "Guessing Words Through Gestures". Thus, this research can concluded that ice-breaking activities were exceptionally appropriated at the beginning of learning, this section could see based on proof of documentation attachments into findings section because all of the researchers could foster students' enthusiasm for have done an ice- breaking before carried out the core learning activities.